2007
DOI: 10.1111/j.1475-1313.2007.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Method for estimating volume of subretinal fluid in cases of localized retinal detachment by OCT ophthalmoscopy

Abstract: The volume of the subretinal fluid can be used to assess the condition of different types of retinal and macular disorders. The purpose of this report is to introduce a method to measure the volume of the subretinal fluid with the images of the optical coherence tomography (OCT) Ophthalmoscope in three cases of central serous chorioretinopathy and one case of retinal pigment epithelial detachment. We used the topography-mode program of the OCT Ophthalmoscope and measured the average height of the retinal detac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The condition generally resolves spontaneously but in some cases, progressive visual loss might develop due to persistent serous retinal detachment, causing degeneration of photoreceptors and retinal pigment epithelial (RPE) cells [2,3]. Previous studies have shown that anatomical and functional assessments of CSC can be achieved by optical coherence tomography (OCT) and multifocal electroretinography (mfERG), respectively [3][4][5][6][7][8][9][10][11][12][13][14][15]. OCT allows non-invasive high-resolution cross-sectional imaging of the macula and provides objective quantitative measurements of retinal morphological changes.…”
Section: Introductionmentioning
confidence: 98%
“…The condition generally resolves spontaneously but in some cases, progressive visual loss might develop due to persistent serous retinal detachment, causing degeneration of photoreceptors and retinal pigment epithelial (RPE) cells [2,3]. Previous studies have shown that anatomical and functional assessments of CSC can be achieved by optical coherence tomography (OCT) and multifocal electroretinography (mfERG), respectively [3][4][5][6][7][8][9][10][11][12][13][14][15]. OCT allows non-invasive high-resolution cross-sectional imaging of the macula and provides objective quantitative measurements of retinal morphological changes.…”
Section: Introductionmentioning
confidence: 98%
“…The characteristics of the intraretinal architecture were analyzed in the subfoveal area (6 mm). We evaluated: loss of integrity of the external limiting membrane (ELM) 11 , absence of small dense particles 12 , loss of the ellipsoid zone integrity, presuming a junction of the external/internal photoreceptor segments 11 , absence of sub retinal thickening (sub retinal thickening defined as a homogenous layer of hyper reflectivity of the band below the ELM, extending to the band representing the pigmented epithelium of the retina -this variable is a qualitative one-), presence of retinal external tubulations 13,14 , absence of vitreomacular traction or epiretinal membrane 15 , presence of retinal pigment epithelium detachment (RPED) 16 , evidence of outer segment stalactites 17 , absence of geographic atrophy, presence of diffuse edema, presence of choroidal thinning or alteration of normal choroidal anatomy based on normal choroidal thickness values 18 (choroidal thickness was measured from the external aspect of the hyper reflective line corresponding to the retinal pigment epithelium (RPE) to the inner side of the subfoveal sclero-choroidal junction, at intervals of 500 from the fovea to the nasal and temporal sector, until completing 5 measurements), absence of intraretinal cysts and sub retinal fluid 19 .…”
Section: Morphological Characteristics By Optical Coherence Tomographymentioning
confidence: 99%
“…Las características de la arquitectura intrarretiniana fueron analizadas en el área subfoveal (6 mm). Se evaluó: pérdida de integridad de la membrana limitante externa (MLE) 11 , ausencia de partículas densas pequeñas 12 , pérdida de la integridad de zona elipsoide presunta unión de los segmentos externos/internos de los fotorreceptores 11 , ausencia de engrosamiento subretiniano (engrosamiento subretiniano definido como una capa homogénea de hiperreflectividad de la banda debajo de la MLE, extendiéndose hasta la banda que representa el epitelio pigmentado de la retina, esta variable es de tipo cualitativa), presencia de tubulaciones externas retinianas 13,14 , ausencia de tracción vitreomacular o membrana epirretiniana 15 , presencia de desprendimiento del epitelio pigmentado de la retina (DEPR) 16 , evidencia de estelactitas de segmentos externos 17 , ausencia de atrofia geográfica, presencia de edema difuso, presencia de adelgazamiento coroideo o alteración de la anatomía normal coroidea basado en los valores de grosor coroideo normales 18 (el grosor coroideo fue medido desde la cara externa de la línea hiperreflectiva correspondiente al Epitelio Pigmentado de la Retina (EPR) hasta la cara interna de la unión esclero-coroidea subfoveal, a intervalos de 500 desde la fóvea al sector nasal y temporal, hasta completar 5 medidas), ausencia de quistes intraretinianos y fluido subretiniano 19 .…”
Section: Características Morfológicas En La Tomografía De Coherencia óPticaunclassified